KSA-Self Assessment of Pain Management Medication Safety for Hospitals - Alomi, Yousef Ahmed; Ibrahim, Eman Kamal (Journal of Pharmacy Practice and Community Medicine)
Pain management program is essential and required the program to prevent the adverse event, drug misadventure, and pain killer medications related death at health care institutions. One of the tools to evaluate the performance and drug safety of the pain management program. It is the assessment of ten directions of medication safety including patient information, medication information, communication process of medicines, drug packaging and labeling, drug devices, work environment and staffing management, competency and education, patient or family education, and quality and risk management. The new tools as self-assessment of pain management medication safety and modified of former the United States of America and Canada Institution Safe Medication Practice (ISMP) ten elements with additional to the health care institution demographic information and according to the pharmacy law and regulations in Saudi Arabia. This new method can assess the hospital's pain management implementation and detect the gap problems implementation, risk of the patient safety level of pain management. The tool had a scoring scale system of acceptable or risk level or need improvement with the annual application. The tool is first self-assessment tool of pain management medication in Saudi Arabia. The tool is highly recommended to apply at all government and private hospitals in Kingdom of Saudi Arabia.
Keywords: Pain Management; Safety; Medications; Self-Assessment; Ministry of Health; Saudi Arabia